2017
DOI: 10.1007/jhep09(2017)157
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning in the string landscape

Abstract: Abstract:We utilize machine learning to study the string landscape. Deep data dives and conjecture generation are proposed as useful frameworks for utilizing machine learning in the landscape, and examples of each are presented. A decision tree accurately predicts the number of weak Fano toric threefolds arising from reflexive polytopes, each of which determines a smooth F-theory compactification, and linear regression generates a previously proven conjecture for the gauge group rank in an ensemble of 4 3 × 2.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
126
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 161 publications
(126 citation statements)
references
References 40 publications
0
126
0
Order By: Relevance
“…It might also be interesting to apply machine learning techniques to investigate the quantum entanglement structure of links studied in [25,26]. Recently, [27][28][29][30] have pioneered investigations of the string landscape with machine learning techniques. Exploring the mathematics landscape in a similar spirit, we expect that the strategy we employ of analyzing correlations between properties of basic objects can suggest new relationships of an approximate form.…”
Section: Discussionmentioning
confidence: 99%
“…It might also be interesting to apply machine learning techniques to investigate the quantum entanglement structure of links studied in [25,26]. Recently, [27][28][29][30] have pioneered investigations of the string landscape with machine learning techniques. Exploring the mathematics landscape in a similar spirit, we expect that the strategy we employ of analyzing correlations between properties of basic objects can suggest new relationships of an approximate form.…”
Section: Discussionmentioning
confidence: 99%
“…In [12] it was shown that genetic algorithms can be utilized to optimize neural network architectures for prediction in physical problems. In [13] it was shown that simpler supervised learning techniques that do not utilize neural networks can lead to rigorous theorems by conjecture generation, such as a theorem regarding the prevalence of E 6 gauge sectors in the ensemble [3] of 10 755 F-theory geometries. Supervised learning was also utilized [11] to predict a central charges in 4d N = 1 SCFTs via volume minimization in gravity duals with toric descriptions.…”
Section: Contentsmentioning
confidence: 99%
“…Given these accurate predictions of n FRST , it is interesting to study the interpretability of the predictions made by the neural network. Sometimes refered to as intelligible artificial intelligence, interpretability is a major current goal of machine learning research, and it is one of the reasons for developing the EQL architecture; see [33] for the related idea of conjecture generation, by which interpretable numerical decisions may be turned into rigorous results. In the EQL context, the idea is to mimic what happens in natural sciences such as physics, where a physical phenomenon is often described in terms of an interpretable function that allows for understanding and generalization.…”
Section: Motivationmentioning
confidence: 99%